The Legal Protection for Debtors in the Implementation of Bad Credit Settlement with Guaranteed Objects of Mortgage - Yulia Sekar Nada (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to find out and analyze the implementation of the settlement of bad loans with mortgage guarantee objects, to find out and analyze legal protection efforts against debtors' assets in the bonds of mortgage certificates to be executed, to identify and analyze weaknesses and solutions for implementing bad loans with objects mortgage guarantee. The approach method in this research is empirical juridical, referring to the literature related to legislation relating to bad loans and research by going directly to the object. The research specification is descriptive analytical, which is a study that seeks to describe in detail the social phenomena whose main problem is without hypotheses and statistical calculations of the required data, the data is taken by methods based on primary data, namely interviews and observations as well as secondary data obtained from literature studies and analyzed qualitatively. The research concluded that the implementation of the settlement of bad loans with the object of guarantee of mortgages was carried out by an auction process through the KPKNL as the last step in efforts to resolve bad loans.